Madame Brulart’s Bastille-bijoux: History and private lives in women’s writings around the French Revolution - Gárdos, Bálint (FOCUS: Papers in English Literary and Cultural Studies, 2024)
My paper offers an interpretation of four novels by women writers (Charlotte Smith, Mary Robinson, Helen Craik) written either during or very shortly after the French revolution. Its aims are briefly the following. 1) To challenge the traditional narrative (associated with Georg Lukács’s seminal study) according to which the historical novel as a genre was created by Walter Scott and responded originally to the shock of the Napoleonic wars. 2) To present a framework in which the pre-historicist (pre-Hegelian) understanding and narrating of history can be understood. This is the classical, rhetorical, exemplary view of history, most readily associated by the eighteenth-century authors with the name of Plutarch. 3) To offer an explanation of the prominence of women authors in the early history of the historical novel. My paper attempts that by emphasising the continuity between the personal and the political that the Plutarchan tradition enabled. Anecdotal, familial, even sentimental elements of such narratives take nothing away from the historical significance of the actors concerned. Women, for whom the initial promise of the transformation in France included the promise of opening up the rigid boundaries separating masculine public world from feminine domesticity used their accounts of the revolution to reinvestigate and reaffirm the continuities between those words.